2015
DOI: 10.1364/boe.6.004923
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative spatial frequency fluorescence imaging in the sub-diffusive domain for image-guided glioma resection

Abstract: Intraoperative 5- aminolevulinic acid induced-Protoporphyrin IX (PpIX) fluorescence guidance enables maximum safe resection of glioblastomas by providing surgeons with real-time tumor optical contrast. However, visual assessment of PpIX fluorescence is subjective and limited by the distorting effects of light attenuation and tissue autofluorescence. We have previously shown that non-invasive point measurements of absolute PpIX concentration identifies residual tumor that is otherwise non-detectable. Here, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…While the current processing time to invert diffuse reflectance maps to optical properties is typically on the order of 1 second, we recently demonstrated that this inversion time could be reduced significantly to approximately 10 ms [31]. Altogether this work lays the foundation of real-time quantitative optical imaging through an endoscope and its clinical translation, potentially enabling endoscopic implementation of current quantitative, widefield techniques [32][33][34].…”
Section: Discussionmentioning
confidence: 85%
“…While the current processing time to invert diffuse reflectance maps to optical properties is typically on the order of 1 second, we recently demonstrated that this inversion time could be reduced significantly to approximately 10 ms [31]. Altogether this work lays the foundation of real-time quantitative optical imaging through an endoscope and its clinical translation, potentially enabling endoscopic implementation of current quantitative, widefield techniques [32][33][34].…”
Section: Discussionmentioning
confidence: 85%
“…Some examples include: using cooled high-dynamic range frame-transfer cameras for rapid and low-signal imaging, using both tunable light sources and hyperspectral cameras for spectral multiplexing, using multiple polarizer orientations to combine with polarization imaging, using commercial projectors to reduce costs, integrating SFDI within existing medical instruments such as surgical microscopes or endoscopes, and using coherent sources to get flow data from speckle. These systems are a combination of benchtop imaging systems with some being transportable to preclinical or clinical sites, 12,[17][18][19][20][21][22][23][24][25] as well as improved methods for robust measurement during clinical conditions [motion correction and three-dimensional (3-D) correction]. 26,27…”
Section: Instrumentationmentioning
confidence: 99%
“…71,72 The concept of using optical properties map from SFDI to quantify fluorescence signals in a co-registered image was introduced early and recently gained interest in the field of fluorescence-guided surgery. 23,73,74 This concept in principle allows quantitative fluorescence, at a subsurface level, to be performed rapidly. Quantitative fluorescence means absolute numbers can be attributed to signal for diagnostic purposes.…”
Section: Sfdi and Fluorescencementioning
confidence: 99%
“…[1][2][3][4][5][6] Some medical fields in particular, such as surgery, are driving this need for realtime interpretable information content to aid decision-making in a time-constrained environment. [7][8][9][10][11][12] Several solutions have been investigated to fulfill this need, each with their pros and cons, ranging from raster scanning of microscopic information to wide-field acquisitions of diffused information. 13,14 For instance, fluorescence imaging to help surgeons visualizing structures of interest, such as lymph nodes, ureters, or micrometastasis, stands as an example where providing tissue-related information in real time plays a key role in clinical adoption.…”
Section: Introductionmentioning
confidence: 99%